(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The corporate sector all over the world is restructuring its operations through different types of consolidation strategies like mergers and acquisitions in order to face challenges posed by the new pattern of globalisation, which has led to the greater integration of national and international markets.. The intensity of cross-border operations recorded an unprecedented surge since the mid-1990s and the same trend continues (World Investment Report, 2000).The objective of the study is to analyse and compare the pre and post-merger and acquisition financial performance of four firms- Ranbaxy, Dr Reddy, Tata Steel and Hindalco through ratio analysis. For this, the data was being collected for three years before and after the acquisition from Capitaline database. Then to compare the changes, SPSS tool- Wilcoxon Signed Rank Test was being applied. The study concluded that cross-border Mergers and Acquisitions of the selected firms have resulted in no significant change in the financial performance of these firms.